Repurposing Institutions through Categorization: New Apprenticeship Programs in Peripheral Service Industries - Nicklich, Manuel; Pekarek, Andreas (Relations industrielles / Industrial Relations, 2025)
The rise of precarious work is an increasing concern for policymakers and researchers, with outsourcing frequently identified as a key driver. In response, skills development and formal qualifications are widely promoted as potential remedies. We examine this development through a categorization lens, focusing on two vocational credentials created for industrial services in Germany. By analyzing how industry actors categorize the work of apprenticeship-qualified employees, we investigate whether recategorizing peripheral jobs as skilled labour effectively addresses precarious employment.We find that the two apprenticeship programs reframe work as skilled and legitimate without substantially improving conditions for workers. Employers may repurpose apprenticeships to serve commercial interests rather than traditional worker-centred roles. This illustrates how institutions can be incrementally reshaped and even undermined through the social negotiation of occupational categories. We demonstrate the applicability of categorization theory to labour markets and work organization, thereby clarifying how recategorization functions as a mechanism of gradual institutional change in precarious sectors. We also show how new apprenticeship programs are strategically positioned within occupational hierarchies, with mixed implications for vocational education reform. Overall, categorization is a contested social process shaped by power asymmetries. While apprenticeships hold symbolic value in elevating work status, the actual reduction of precarity remains limited. The challenges of precarious employment are reinforced rather than resolved.